Pengaruh Labelisasi Halal, Kualitas Produk, Word Of Mouth (WOM) Dan Harga Terhadap Minat Beli (Studi Kasus Pada Pengguna Lip Cream Hanasui Varian Boba Edition Di Kelurahan Gadang Kota Malang) - Wahyuni, Mauliddiah Dwi; Rachma, N.; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Thisistudyiaimsitoidetermineiand analyzeitheiinfluence of halal labeling, productiquality,iword of mouth, and price on consumer purchase intention of Hanasui Boba Edition lip cream in Gadang sub-district, Malang city. This study employed quantitative research with descriptive analysis. The population was Hanasui Boba Edition lip cream users in Gadang sub-district, Malang city. A purposive sampling technique was used for the sample size, with 95 respondents. Primary data were collected using a questionnaire. The results showed thatihalalilabeling, productiqualityiword of mouth, and price significantly influenced purchase intention. Halal labeling significantly influenced purchase intention. Product quality significantly influenced purchase intention. Word of mouth significantly influenced purchase intention. Price significantly influenced purchase intention. Keywords: Halal Labeling, Product Quality, Word of Mouth, Price, and Purchase Intention